Reinvestigation of Electric Field‐Induced Optical Activity in α‐Quartz: Application of a Polarimeter With Four Photoelastic Modulators. Issue 9 (26th November 2013) - Gupta, Arnab Sen; Arteaga, Oriol; Haislmaier, Ryan; Kahr, Bart; Gopalan, Venkatraman
ABSTRACT Linear electrogyration (electric field‐induced optical activity) and electro‐optic effects in x‐cut and z‐cut right‐handed (RH) α‐quartz were measured using a complete Mueller matrix polarimeter. The polarimeter used in the analysis was equipped with four photoelastic modulators operating at different frequencies. This configuration is especially sensitive due to the fidelity of the modulators and the fact that all the Mueller matrix elements can be delivered without any moving optical elements. The linear electrogyration coefficient γ11 as a function of the wavelength of incident light was remeasured. The coefficient γ33, required by symmetry to be zero, was evaluated as a control. γ11 was much smaller than values obtained previously using devices dependent on mechanical light modulation. Electrogyration measurements have often been confounded by the much larger linear electro‐optic effect. The Mueller calculus used herein is well suited to the separation of the competing changes to the polarization state of light. Quadratic electrogyration associated with elements β11 and β33 was not detectable. Chirality 26:70–73, 2013. © 2013 Wiley Periodicals, Inc.